Pengembangan Model Pembelajaran Ecoprint untuk Meningkatakan Keterampilan Abad 21 di Sekolah Dasar - Widiantoro, Slamet (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this research is to develop project-based learning media (Project Based Learning) to improve communication skills, collaboration, critical thinking, and creativity of 4th grade elementary school students. The method used is ADDIE (Analysis, Design, Development for Production, Implementation and Evaluation). Data collection is done by questionnaire, observation and performance tests. Descriptive qualitative analysis techniques. This research produces ecoprint media which is used for project-based learning. The results of the implementation of the ecoprint media can enhance creativity, communication, collaboration, and critical thinking.